Variabilitas Genetik dan Heritabilitas Karakter Agronomi Kedelai (Glycine max [L.] Merrill) Generasi F5 Hasil Persilangan WILIS X B3570 - Meydina, Aulia; Barmawi, Maimun; Sa?diyah, Nyimas (Politeknik Negeri Lampung., 2015)
The purpose of this study was to determine the amount of genetic diversity and phenotype, heritability in a broad sense as well as the numbers of soybean expectations F5 generation from crosses Wilis × B3570 which has a middle value the better of both parents. The experimental design used randomized group design by three replications. Genotypes were tested as much as 25 genotypes. he results showed that the amount of genetic diversity of soybean agronomic characters F5 generation from crosses Wilis x B3570 found in almost all the characters except the characters age observed flowering and harvesting age. The genotype diversity found in all agronomic characters were observed. The magnitude of the high heritability values found in the character of a weight of 100 grains. Heritability values were on plant height, number of productive branches, and the total number of pods. Character weight of seeds per plant, flowering age, and time of harvest had the lowest heritability. Numbers expectation obtained by the genotypes number 163-1-4, 130-2-11, 130-2-11, 163-1-15, 102-3-2, 163-1-1, 140-1-15 , 163-1-6, 181-5-4, 140-1-2 are rated according to the weight of the weight of seeds per plant that would refer to the high production Kata kunci: variability and heritability, and Soybean